Depression and its Associated Factors among Older People Residing in Household Level of Chitwan District, Nepal - Chapagain, Shakuntala; Khanal, Deena; Paudel, Binaya; Paudel, Isha; Mali, Prajita; Khanal, Gayatri; Chhetri, Mamata (Journal of Karnali Academy of Health Sciences, 2022)
Background: Worldwide, with the rapidly growing elderly population, depression is becoming a major public health problem. This study aimed to find depression and its associated factors among older people. Method: Community based cross-sectional study was conducted in Chitwan District. Multi-stage sampling technique was used. Out of 7, three Municipalities were selected by using a simple random sampling method. Wards from each selected Municipabilities were taken by using a simple random sampling method. Participants from each selected ward were taken conveniently. The sample size of the study was 318. Data were collected through face-to-face interviews using a semi-structured questionnaire. For assessing depression, a standard and scientific tool (Geriatric depression scale-15) was applied. Ethical approval was obtained from the Institutional Review Committee of Chitwan Medical College (Ref: CMC-l RCl07 6107 7 – 134). Data collection was done from December 16, 2020 to February 16, 2021. Data were analyzed by using descriptive and inferential statistics like frequency, percentage, chi-square and linear regression. Results: Out of total of 318 selected older participants, nearly half (49.4%) had depression. Among total participants, 33 (10.38%), 18 (5.6%) and 106 (33.3%) had mild, moderate and severe depression respectively. Ethnicity (p=0.004), Marital status (p<0.001), education status (p=0.001), occupation before 60 years of age (p=0.001), individual income (p=0.001), living arrangement (p=0.001), family member behavior (p=0.001), feeling of loneliness (p=0.001) and functional capacity (p<0.001) are found to be associated with depression. Conclusion: Very high number of people suffered from depression and age, education, marital status, individual income, and occupation before 60 years of age has a profound relationship with depression.